2003
DOI: 10.1046/j.1365-2958.2003.03775.x
|View full text |Cite
|
Sign up to set email alerts
|

The quaternary structure of RNase G from Escherichia coli

Abstract: SummaryRNase G is the endoribonuclease responsible for forming the mature 5 ¢ ¢ ¢ ¢ end of 16S rRNA. This enzyme shares 35% identity with and 50% similarity to the Nterminal 470 amino acids encompassing the catalytic domain of RNase E, the major endonuclease in Escherichia coli . In this study, we developed nondenaturing purifications for overexpressed RNase G. Using mass spectrometry and N-terminal sequencing, we unambiguously identified the N-terminal sequence of the protein and found that translation is ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…Assuming a crosslinking efficiency of 63% for multimeric RNase G under these reaction conditions, the data suggest that, unlike N-RNase E, this protein exists almost entirely as a dimer or higher-order multimer at the concentrations tested. This finding is consistent with recent sedimentation velocity studies (16) and with the lack of a significant effect of enzyme concentration on the marked 5Ј-end dependence of RNase G within this concentration range (Fig. 4B).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Assuming a crosslinking efficiency of 63% for multimeric RNase G under these reaction conditions, the data suggest that, unlike N-RNase E, this protein exists almost entirely as a dimer or higher-order multimer at the concentrations tested. This finding is consistent with recent sedimentation velocity studies (16) and with the lack of a significant effect of enzyme concentration on the marked 5Ј-end dependence of RNase G within this concentration range (Fig. 4B).…”
Section: Resultssupporting
confidence: 82%
“…Of relevance to this hypothesis are recent studies showing that RNase G exists primarily as a homodimer at moderate protein concentrations (16) and that N-RNase E exists primarily as a homotetramer at very high protein concentrations (17). That N-RNase E at lower concentrations can exist as a mixture of protein forms in different multimeric states was indicated by the results of gel electrophoresis under nondenaturing conditions, which revealed both monomeric and dimeric forms of the protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, as predicted from the experiments in B. subtilis (Pellegrini et al, 2003), the enzyme does not process a B. subtilis tRNA precursor sibly RNase Z and RNase LS, the most likely explanation for their apparent supporting role in mRNA decay in single mutants (Table 1, Ow et al, 2003;Otsuka and Yonesaki, 2005) arises from the relatively low abundance of these proteins. Clearly this is probably the case with RNase G (Briant et al, 2003), where overproduction of the protein was shown to decrease the half-life of the rpsT mRNA in an rne-1 mutant (Ow et al, 2003). Alternatively, initial RNase E cleavages may generate substrates that are more efficiently cleaved by RNase Z, RNase G and RNase LS.…”
Section: Discussionmentioning
confidence: 99%
“…3). Furthermore, not withstanding previous reports that six extra amino acids at the amino terminus of RNase G (a situation that does not occur in vivo) (Briant et al 2003) led to complementation of RNase E mutants (Lee et al 2002;Deana and Belasco 2004), this modified protein did not effectively complement the rne-1 allele at 44°C in the MG1693 genetic background (Fig. 3).…”
Section: Discussionmentioning
confidence: 72%
“…The chromosomal rng sequence is shown at the top. The native translation start, identified by sequencing of the protein purified from E. coli (Briant et al 2003) is shown as +1. The translation start site employed by Lee et al (2002) and Deana and Belasco (2004) is indicated as À18.…”
Section: Resultsmentioning
confidence: 99%